Highly Flexible, Large‐Area, and Facile Textile‐Based Hybrid Nanogenerator with Cascaded Piezoelectric and Triboelectric Units for Mechanical Energy Harvesting. Issue 6 (14th April 2018) - Song, Jian; Yang, Bao; Zeng, Wei; Peng, Zehua; Lin, Shuping; Li, Jun; Tao, Xiaoming
Abstract: Despite of the rapid development and demonstrations of wearable energy harvesting devices, their industrial applications are limited by the lack of highly flexible, scalable, and facile fabrication methods. Especially, few studies have combined theoretical analysis with the relevant experimental verification. To this end, a highly flexible and large‐area textile‐based hybrid nanogenerator integrated a net‐shaped nanofiber reinforced piezoelectric unit and a triboelectric unit with a microstructured surface configuration is demonstrated. Electrospinning is used to fabricate an optimized Polyvinylidenefluoride (PVDF)‐carbon nanotube (CNT)‐BaTiO3 nanofiber/particle nonwoven fabric of 18 cm × 27 cm for the piezoelectric unit without further polarization. Then a large‐area freestanding Polydimethylsiloxane (PDMS)‐multiwall CNT‐graphite flexible composite film of 20 cm × 25 cm, optimized for the triboelectric unit is prepared by the doctor‐blading method. The resultant hybrid nanogenerator, 4.5 cm × 5 cm in size, generates a rectified average peak output voltage of 161.66 V, along with the highest peak power output of 2.22 W m −2, directly driving 150 light‐emitting diodes (LEDs). Importantly, an explicit theoretical model for the hybrid nanogenerator is proposed and good agreements are obtained between the theoretical and the corresponding experimental results, which shed new light on the mechanism and predict ways to optimize such hybrid nanogenerators. Abstract : A novel highly flexible and large‐area textile‐based hybrid nanogenerator is fabricated, consisting of piezoelectric nanofiber fabric and a freestanding triboelectric layer. An explicit theoretical model is presented with good agreements between the theoretical and the corresponding experimental results.